Impact of Material and Lens Design on Repositioning Surgery of Toric Intraocular Lenses: A Single-Arm Meta-Analysis - Jing Wu; Changping Yang; Yan Yin; Linlin Liu; Hui Wang (Journal of Ophthalmology)
Aim. To analyze the pooled incidence rate in repositioning surgery by considering different materials and designs. Methods. All published studies investigating the repositioning surgery of toric intraocular lenses (IOLs) before September 1, 2020, were searched and evaluated. The R3.5.2 software was used to extract the data, and a single arm meta-analysis was performed. Results. 19 cases from 18 published studies articles were included in the meta-analysis. The pooled incidence rate in repositioning surgery was 2% (I2 = 53%, Pheterogeneity<0.01). Plate and silicone IOLs had significantly higher incidence rates (6% for each) than loop (2%) and hydrophobic acrylate (2%). Incidence rates of Acrysof, Staar, TECNIS, PhysIOL SA, T-flex 623T, and Microsil 6116TU groups were 1% (95% CI [1%–2%]), 6% (95% CI [4%–9%]), 3% (95% CI [2%–4%]), 1.40% (1/71), 3.03% (1/33), and 4.76% (1/21), respectively. Conclusions. The pooled incidence rate of repositioning surgery in IOLs was 2%. Materials and designs would be risk factors for the rotational stability of the toric IOLs. Pooled incidence rates of the hydrophobic acrylate and loop group were lower than those of the silicone and plate group. Product identity is the main driver of heterogeneity.